2014
DOI: 10.1002/rra.2771
|View full text |Cite
|
Sign up to set email alerts
|

Armour Layer Analysis of Local Scour around Bridge Abutments Under Ice Cover

Abstract: A set of experiments was conducted for the local scour around bridge abutments under ice cover in non‐uniform sediments. By taking into account of the grain size of the armour layer and ice cover roughness, the dimensionless maximum scour depth is analysed. With an increase in grain size of the armour layer, the dimensionless maximum scour depth decreases. With the increase in ice cover roughness, the dimensionless maximum scour depth increases correspondingly. By using dimensional analysis, a regression relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…With decrease in D50 of the original sand, the grain size of the armour layer decreases correspondingly. These results are in good agreement with findings of Wu et al (2015) who investigated the armour layer in scour holes around square and semi-circular abutments.…”
Section: Grain Size Analysis Of Armour Layersupporting
confidence: 92%
“…With decrease in D50 of the original sand, the grain size of the armour layer decreases correspondingly. These results are in good agreement with findings of Wu et al (2015) who investigated the armour layer in scour holes around square and semi-circular abutments.…”
Section: Grain Size Analysis Of Armour Layersupporting
confidence: 92%
“…It was observed that after about a period of 6 h, scour hole reached to the equilibrium state and no significant changes were observed in scour depth. However, the running experimental time for the present experiments was 24 h to be compatible with the experimental results of Wu et al [51].…”
Section: The Incipient Motion Of Sediment Particles Under Ice-coveredsupporting
confidence: 90%
“…River ice hydrology has been an implicit part in ice engineering. Some studies on ice engineering research can be found in the references [1,12,22,9,21,23,26,30,32]. To date, the mechanism of local scour around bridge abutments and piers under ice cover is still not well understood.…”
Section: Impact Of Ice Covermentioning
confidence: 99%
“…As suggested by Wu et al [30], the following relationships were developed to show the maximum scour depth under ice cover around square and round abutments:…”
Section: Effects Of Sediment Transport On Hydraulic Structuresmentioning
confidence: 99%